GENDERED AI GOVERNANCE: INDONESIA'S HUMAN SECURITY FRAMEWORK - Herdiansyah Hamzah; Muhammad Yuga (Jurnal Paradigma Hukum Pembangunan, 2026)
The concept of human security, first articulated by Mahbub-ul-Haq in the United Nations Development Programme's Human Development Report in 1994, emphasizes freedom from fear and freedom from want as cardinal principles, positioning individuals as the primary referent in security discourse. As artificial intelligence systems rapidly proliferate across Indonesia, these foundational human security concerns have manifested in distinctly gendered dimensions that demand urgent regulatory attention. This article examines the critical intersection between gender, human security, and AI governance in Indonesia's evolving regulatory landscape. Through systematic analysis of algorithmic discrimination cases affecting Indonesian women, particularly in the gig economy and online gender-based violence contexts, this research establishes the imperative for integrating gendered human security frameworks into national AI regulation. The study employs doctrinal legal research methodology combined with intersectional feminist analysis to propose a three-pillar regulatory model encompassing gender-responsive Smart Mix Approach, mandatory Human Rights Due Diligence, and gender-sensitive Regulatory Sandbox mechanisms. Findings reveal significant gender bias in AI systems, with online gender-based violence cases surging by 80.8 percent in 2024. The article argues that constitutional obligations under Indonesia's 1945 Constitution necessitate explicit gender mainstreaming in AI governance to protect women's fundamental rights from algorithmic discrimination.